ECOLOGICAL IMPLICATIONS OF FISH AND GEAR DIVERSITY IN SHIRORO DAM RESERVOIR, NIGER STATE, NIGERIA - Ibrahim, A.; Yusuf, J.; Ibrahim, S. U.; Yakubu, U. P.; Yisa, T. A.; Olowoyo, E. T. (Nigerian Journal of Fisheries, 2018)
The natural biodiversity of the aquatic ecosystems in Nigeria has encountered changes in stock diversity and trophic composition due to fragmentation and overexploitation. These changes have resulted in the disappearance and dominance of species. This study was designed to assess the fish and gear diversity of the Shiroro Dam Reservoir (SDR) and provide empirical data for the management and sustainability of the natural fish resources. A structured questionnaire was used to obtain data on fishes and gears from selected/respondent fishers at the landing site monthly. Gillnets (Gn), Malian traps (Mt), and Cast nets (Cn) were the main gears identified in SDR. Each of Gn and Mt had a 33 % user preference against the 27 % for Cn. A higher percentage (60 %) of the fishers used gears following the state's allowable mesh size (5.0 - 9.99 cm) regulations. Collected fish samples comprised 20 species in 16 genera, 13 families, and 7- orders. Species diversity was generally low; 1-D: 0.11- 0.56. The guild composition: 27.20 % Herbivores, 21.59 % carnivores, and 51.20 % omnivores indicate trophic imbalance (low F/C ratio). Hence, the need to control the carnivore's population and introduce a Community-Based Fisheries Management Approach with cross-scale linkages.